Effect of nickel chloride on streptozotocin-induced diabetes in rats - Novelli, E. L.B.; Rodrigues, N. L.; Ribas, B. O. (Canadian Science Publishing, 1988)
The potential of nickel chloride to prevent streptozotocin-induced hyperglycemia was tested in rats in vivo. To induce diabetes, streptozotocin (100 mg/kg body weight) was injected as a single dose. Streptozotocin treatment resulted in a significant decrease in plasma insulin and ceruloplasmin, and pancreatic Cu, protein, and Cu-Zn superoxide dismutase activity. In rats treated with nickel chloride (10 mg/kg body weight) and streptozotocin, these values were comparable with those observed in control rats. The results indicate that nickel chloride injected before streptozotocin prevented streptozotocin-induced hyperglycemia, and suggest that the protective effect was related to Cu-Zn superoxide dismutase activity, mediated by copper.